Children’s agency in reducing poverty and environmental risk: Case study of Islamic Relief South Africa’s Orphan Sponsorship Programme. - Lombard, A. (Antoinette) (University of Pretoria, 2021)
Mini Dissertation (MSW (Social Development and Policy))--University of Pretoria, 2020.